Pertumbuhan dan Hasil Bayam (Amaranthus cruentus L) Akibat Pemanfaatan Bahan Organik Cair Hasil Fermentasi Isi Rumen - Laurensius Lehar (Jurnal Penelitian Pertanian Terapan, 2010)
The research has been done to evaluate the growth and yield of amaranth (Amaranthus cruentus L) as application effect of liquid organic matter from rumen substance fermentation. The objectives of the research were to know: 1) The composition of Liquid organic matter (LOM) that produced from Leguminous (Lamtoro and Gamal) fermented by rumen substance, 2) The effect of the leguminous of LOM on growth and yield of Amaranth. The research used a Completely Randomized Design (CRD) with 5 treatments and times replicated. The treatments were : 1) Control (no added by LOM), 2) 6 ml L-1of LOM, 3) 12 ml L-1of LOM, 4) 18 ml L-1of LOM, and 5) 24 ml L-1 of LOM. Variable Reponses observed were : 1) The Leaf Area Index (LAI), 2) Net Asimilasi Rate (NAR), 3) Relative Growth Rate (RGR), 4) Fresh Weight of Amaranth, 5) N-P-K contents of soil before planting, and 6) N-P-K contents of Amaranth. The result showed that : 1) The LOM contents were 7.98% Nitrogen (N), 99.5ppm Phosphor (P), and 1.70 me (100g) -1 Kalium (K) ; 2) Application of LOM increased the LAI, RGR, and Fresh weight of Amaranth; 3) The concentration of LOM on 24 ml L-1, produced 11.8485 cm2g-1 of LAI, 0.08975 g cm2 day -1 of NAR, 0.927 g g-1 day -1 of RGR, and 21.675 g of fresh weight of Amaranth at Â 30 days after transplanting with total nutrients absorbed 2.855% N, 522.26 ppm P, and 25.13 me (100)-1K.Â Keywords: amaranth, liquid organic, rumen substance fermentation